Investigating the effect of shape, orientation and position of an island on spiral tool path. (2018) - Patel, Mayur M.; Patel, Divyangkumar D.; Dodiya, Hardik R.; Lalwani, D.I.
Abstract: Pocket machining is widely used in aerospace, shipyard, automobile, die and mould industries. In high speed pocket machining, the preferred tool path is one that has least number of sharp turn. The conventional tool path, e.g. directional parallel or contour parallel, has various drawbacks such as rise in the cutting load, stop and go motion of cutter, shorter tool life. However, the spiral tool path overcomes the above mentioned drawbacks. The presence of island inside a pocket greatly affects the generation of spiral tool path. Therefore, in the present work the effect of shape, orientation and position of an island inside a pocket is studied. The spiral tool path is generated in MASTERCAM TM X6. The resultant tool paths are observed and comparative study of tool paths is carried out.